PENGARUH CURRENT RATIO, DEBT TO ASSET RATIO, DAN TOTAL ASSET TURN OVER TERHADAP NET INCOME GROWTH PADA PT PLN (PERSERO) WILAYAH KALIMANTAN TIMUR DAN KALIMANTAN UTARA AREA BONTANG - Mahmudah, Istianatul; Harianto, Rudy Pudjut (Arthavidya Jurnal Ilmiah Ekonomi, 2016)
Abstract : This research aims to analyze the effect of Current Ratio, Debtto Asset Ratio, and Total Asset Turn Over toward Net Income Growth onPT. PLN (Persero) Region East and North Borneo at Bontang Area.Data Analyse method that used in this research are classical assumptiontest (normality, multicollinierity, heteroscedasticity, autocorrelation) andMultiple Linier Regression Analyse (correlation coeficient, determinationcoeficient, F test/varians analyse, t test/significantion test).Accumulatively, coeficient correlation (R) = 0,385 so that it can be saidthat the independent variables toward dependent variable in thisresearch can giving the weak correlation. Result of Test Varians (F)express the Ho refused because Fcount < Ftable or 0,464 < 4,066. Itsmeaning that variable of Current Ratio, variable of Debt to Asset Ratio,and variable of Total Asset Turn Over by together didn’t have theinfluence which significant to Net Income Growth variable.The result of significantion test could be explained : (1) there are not asignificant effect of Current Ratio on Net Income Growth (2) there arenot a significant effect of Debt to Asset Ratio on Net Income Growth (3)there are not a significant effect of Total Asset Turn Over on Net IncomeGrowth.Keywords : Current Ratio, Debt to Asset Ratio, Total Asset Turn Over,Net Income Growth.